The statistical correlations of rate of change of TEC index (ROTI) on the standard scintillation indices over the Canadian Arctic - Wang, Yong; Jayachandran, P. T.; Wang, Fei-Fei; Zhang, Q.-H.; Sun, Shu-Ji; Xu, Tong; Xing, Zan-Yang; Ma, Yu-Zhang; Ruohoniemi, J. M.; Shepherd, S. G. (Frontiers in Astronomy and Space Sciences, 2025)
For decades, the Rate of Change of Total Electron Content Index (ROTI) has been employed to monitor and quantify ionospheric irregularities, serving as a potential substitute for standard scintillation indices. However, to date, ROTI has not been sufficiently investigated in terms of its relationship with standard scintillation indices. This study presents a preliminarily statistical analysis of the relationship between ROTI and standard scintillation indices using GPS receivers from the Canadian High Arctic Ionospheric Network (CHAIN) over a 5-year period from 2011 to 2015. Our results show that as ROTI increases, the phase scintillation index (σφ) exhibits a corresponding linear increase (slope of ∼0.34), while the amplitude scintillation index (S4) shows little to no enhancement (slope of ∼0.05). Both relationships exhibit high correlation, with coefficients of approximately 0.93 and 0.82, respectively. The differentiated responses suggest that the significant enhancement of standard phase scintillation index is fundamentally dominated by refractive effects, which is primarily driven by large-scale ionospheric structures (>Fresnel-scale probably). The feeble inflation of S4 supports the assertion. Accordingly, the linear relationship solely between ROTI and σφ suggests that the increase in ROTI can be used to empirically assess the contribution of refractive variations to the enhancement of σφ at high latitudes.